Tailored Approaches towards the Synthesis of l‐S‐(Trifluoromethyl)cysteine‐ and l‐Trifluoromethionine‐Containing Peptides. Issue 2 (13th December 2016) - Gadais, Charlène; Saraiva‐Rosa, Nathalie; Chelain, Evelyne; Pytkowicz, Julien; Brigaud, Thierry
Abstract : Among the fluorinated noncanonical amino acids, l ‐trifluoromethionine (TFM) andl ‐ S ‐(trifluoromethyl)cysteine (TfmCys), fluorinated analogues of methionine and cysteine, are of particular interest because of their ability to locally increase the hydrophobicity of peptides. We report herein the synthesis of tert ‐butoxycarbonyl/benzyl‐protected TFM and TfmCys by using a cheap and user‐friendly radical trifluoromethylation approach. The benzyl protecting group of these fluorinated amino acids could be conveniently removed by hydrogenolysis, which circumvented troublesome saponification reactions. For the first time, TfmCys was inserted into a peptide sequence by liquid‐ or solid‐phase peptide synthesis. Finally, a late trifluoromethylation strategy with the use of Togni's reagent on disulfide‐bridged peptides was also efficient to incorporate TFM or TfmCys at both N‐terminal and internal positions. Abstract : l ‐Trifluoromethionine (TFM) andl ‐ S ‐(trifluoromethyl)cysteine (TfmCys) are synthesized by radical trifluoromethylation. TfmCys is inserted into the peptide sequence by liquid‐ or solid‐phase peptide synthesis (SPPS). A late trifluoromethylation strategy with Togni's reagent on disulfide‐bridged peptides is efficient for the incorporation of TFM or TfmCys at both N‐terminal and internal positions.